Asymptomatic course of overt primary hypothyroidism with a very high peak systolic velocity of the superior thyroid arteries: A case report - Ushakov, Andrey (Indian Journal of Case Reports, 2024)
This study reports the case of a 59-year-old woman with asymptomatic overt hypothyroidism who presented with signs of increased thyroid exertion involving the autonomic nervous system. These signs included significantly increased peak systolic velocity (PSV) of the superior thyroid arteries (STA) and moderately increased blood flow intensity. The findings suggest an increase in the rate of thyroxine deiodination and the sufficiency of free triiodothyronine (FT3) for the functional needs of the body. The absence of typical symptoms of hypothyroidism may depend on the sufficiency of FT3 in the serum and additional nonhormonal circumstances. Hence, FT3 should always be measured in addition to thyroid-stimulating hormone and free thyroxine levels. When Doppler ultrasound is used, the intensity of blood flow and PSV-STA from both sides should be determined to assess the magnitude of thyroid exertion. Probably, PSV-STA may not be an absolute criterion for the diagnosis of Graves’ disease.